GRAMMATICAL ERRORS ON THE THESIS - Batdal Niati; Eripuddin Eripuddin (INTERNATIONAL JOURNAL ON LANGUAGE, RESEARCH AND EDUCATION STUDIES, 2019)
. Grammatical errors on thesis almost happen in the entire thesis chapters. This case need to be analyzed in descriptive qualitative design. The purpose of the research was to find out grammatical errors types and factors influence it. The samples were selected randomly; 18 theses and students. Interview and documentation were as the instruments to collect data. The data were analyzed by indicators of the experts’ theories. Finding showed that error occurred in tenses, preposition, and punctuation. The most error was error in tenses. Causes of errors were inter-lingual transfer (mother tongue), intra-lingual, careless, and translation. Carelessness was the main cause of errors. The findings was as references in teaching grammar subject.Keywords: Grammatical Error, Causes of Errors, Thesis